2 i
If the value of the expression above is equal to a + b i , where a and b are real numbers, find the value of a + b .
Clarification : i = − 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Very nice solution! This was a very clever way of solving this problem and I love the wittiness in this solution. Much simpler than mine. However, maybe you could try to go one step further like so:
2 i = i 2 + 2 i + 1 = ( 1 + i ) 2 = 1 + i
Just a suggestion.
Wonderful solution!
Log in to reply
Edited...... BTW Thanks.
When rewriting a complex number in an alternate form, it is always helpful to first rewrite it as z = e ln ( z ) . Executing:
2 i = ( 2 i ) 2 1 = e 2 1 ln ( 2 i ) = e 2 1 ( ln 2 + ln i ) = e ln 2 + 2 1 ln ( i ) = exp ( ln 2 + 4 i π )
Using the definition of the complex logarithm Log ( z ) = ln ∣ z ∣ + i Arg ( z ) we can see that ln ∣ z ∣ = ln 2 and i Arg ( z ) = 4 i π . So, we need to come up with some complex number with a modulus of 2 and an argument of 4 i π . We know that the argument of z is ∣ a + i b ∣ = a 2 + b 2 so let's generate some possible values of a and b that will sum to 2. Well, if a = 1 and b = 1 then a 2 + b 2 = 2 . Simple. However, we don't know if these numbers will generate the argument required. let's check.
Let's picture our potential complex number as a vector in the complex plane. We have an ı ^ -component (real part) of 1 and a ȷ ^ -component (imaginary part) of 1. Using the definition of tangent we see that
tan θ = adjacent opposite ⇒ tan θ = 1 → θ = 4 π
So everything checks out and our guess is correct! Therefore a = b = 1 and so 2 i = 1 + i
a + b = ℜ [ a + i b ] + ℑ [ a + i b ] = 2
2 i = 2 e 2 i π = 2 ⋅ e 4 i π = 2 ( cos 4 π + i sin 4 π ) = = 2 ( 2 2 + i 2 2 ) = 1 + i ⇒ a = b = 1 ⇒ a + b = 2
2 i = 2 c i s ( 2 π ) 2 ⋅ ( 2 1 + 2 i ) 1 + i 1 + 1 = 2
Problem Loading...
Note Loading...
Set Loading...
Using i 2 + 1 = 0 2 i = i 2 + 2 i + 1 = ( i + 1 ) 2 = i + 1 a = b = 1 or a + b = 2